Can information improve rural governance and service delivery? - Kosec, Katrina; Wantchekon, Leonard (Elsevier, 2020)
In the context of an exponential rise in access to information in the last two decades, this special issue explores when and how information might be harnessed to improve governance and public service delivery in rural areas. Information is a critical component of government and citizens’ decision-making; therefore, improvements in its availability and reliability stand to benefit many dimensions of governance, including service delivery. Service delivery is especially difficult in rural areas which contain the majority of the world’s poor but face unique logistical challenges due to their remoteness. We review the features of the recent information revolution, including increased access to information due to both technological and institutional innovations. We then raise the question of why information often fails to support the goals of improved governance and service delivery. We argue that information alone is insufficient. To be impactful, the information must be deemed relevant, in the sense of being salient and having a high perceived signal-to-noise ratio, and individuals must have both the power and incentives to act on it. Bringing all three of these factors together in any setting is challenging, particularly for rural areas, where capacity to receive, understand, and act on information is relatively low. Research failing to find significant effects of greater access to information on rural governance and service delivery has largely failed due to one of these three factors not being in place. This interpretation is broadly supported by our review of 48 empirical studies on the impacts of information on governance and service delivery. We conclude by discussing broader lessons for both development research, including randomized control trials, and the development process itself. The goals of interventions to provide information may need to be more modest, and their design may merit more scrutiny.